Vaishnavism of the Gowd Saraswat Brahmins and a Few Konkani Folklore Tales - Chavan, V.P., (Brill | Manohar Publishers & Distributors, 2024)
Gowd Saraswat Brahmins (GSB) have contributed immensely to the Konkani literature. But after the Portuguese conquest of Goa in 1500, it further transformed Konkani into a vernacular language of the majority of Goan population. This book delves about the history of Gowd Saraswat Brahmin community and their affiliation towards Vaishnavism sect, as the community adopted the principles of the twelfth century ascetic Madhavacharya. The later part contains six classical folk tales collected from the Konkani literature, which is the significant part of this book.